MOTIVASI MAHASISWA MELANJUTKAN PENDIDIKAN KE IKIP MUHAMMADIYAH MAUMERE PROGRAM STUDI PENDIDIKAN EKONOMI ANGKATAN 2022: MOTIVASI MAHASISWA MELANJUTKAN PENDIDIKAN KE IKIP MUHAMMADIYAH MAUMERE PROGRAM STUDI PENDIDIKAN EKONOMI ANGKATAN 2022 - Yasir Arafat (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Student Motivation to Continue Education at IKIP Muhammadiyah Maumere Economic Education Study Program Class of 2022. Paper. Maumere: Faculty of Education of Social Sciences and Humanities Maumere Muhammadiyah Institute, 2023. This study aims to determine the motivation among students of the IKIP Muhammadiyah Maumere Economic Education Study Program Class of 2022 in continuing their education. The subjects of this research were 10 students from batch 2022 of the Economics Education Study Program, IKIP Muhammadiyah Maumere. This research use desciptive qualitative approach. The instruments used in this study were observation, interviews and documentation. The results of this study show that there are two motivations for students who continue their education at the IKIP Muhammadiyah Maumere campus for the economic education study program class of 2022, in general there are two, namely motivation that is in accordance with ideals (goal direction), and motivation that is not in accordance with ideals. Differences in the motivation of students who continue their education at the IKIP Muhammadiyah Maumere program for economic education studies class of 2022 such as no initial motivation, different orientation, or other needs apart from the initial motivation gave birth to four different levels of needs, namely self-actualization, appreciation, social needs, and feeling safe.